ANALISIS TENTANG NILAI-NILAI KARAKTER BANGSA PADA BUDAYA PACU JAWI DINAGARI PARIANGAN KECAMATAN PARIANGAN KABUPATENTANAH DATAR - Anugrah Alfariez Alfariez; Sri Erlinda Erlinda; Hambali ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This research is based on the establishment and changing character is not happen by itself. Character is build from the relation with an object, person, group, value, individual relation, group relation, and there are so many possibilities that influence the character in Pacu Jawi culture on Pariangan, the formulation of this research is, is there are nation values in Pacu Jawi culture on Pariangan, Pariangan district Tanah Datar regency? Also, the aim of this research is to know the character nation values in Pacu Jawi culture in Pariangan, Pariangan district Tanah Datar regency. The population of the research is societies in Pariangan with people whom 18-65 years old, 4.151 souls. Writer takes the Earl Babbie (Prijana, 2005) theory, to takes relevant sample in qualitative research, “sampling is the process selecting”. The selecting process is to get people, situation, activities, and document that writer get from the people who able to express it, or number of population then chose based on the aim and people who relevant to the problem. Based on Earl Babbie, the researcher allowed to takes the sample with purposive sampling technique and researcher takes 70 souls. The data collected from observation, questionnaire, interview, and library technique. The data analyzed with qualitative descriptive analysis. The result of this research show that there are character nation values in Pacu Jawi culture on Pariangan, Pariangan district Tanah Datar. The values contained in the culture ox runway are : Value of religious, honest, tolerance, discipline, hard work, independent, democratic, national spirit, friendly, peace-loving, caring enviroment, social care, responsibility. So the hypothesis that there is nation of character values in Culture Pacu Jawi in Nagari Pariangan Pariangan District of Tanah Datar. Keywords: nation character, culture, pacu jawi